IMPLEMENTATION OF THE MONITORING CENTER FOR PREVENTION AS A MODERATING DETERMINANT OF FRAUD PREVENTION - Endar Pituringsih; Prayitno Basuki; Akram; Liga Ayun Selatan (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
This study examines the effect of Leadership Style, Ethical Management Culture, and Internal Control System on Fraud Prevention, moderated by the Monitoring Center for Prevention (MCP) in each Regency/City across Lombok Island. The population of this study consists of two thousand one hundred twenty-four employees. Then, the sample was selected using a non-probability purposive sampling technique, resulting in 100 respondents. The research data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Therefore, this study resulted that, partially, Ethical Management Culture and Internal Control System positively affect Fraud Prevention. Whereas this study found that Leadership Style has a negative effect. Furthermore, its finding indicates that implementing the Monitoring Center for Prevention (MCP) has not been able to moderate the determinants of Fraud Prevention within local governments in the Regencies and Cities across Lombok Island. So, the local governments throughout Lombok Island need to enhance their evaluation and supervision efforts. The fraudulent acts can be prevented and minimized, thereby avoiding losses that could ultimately lead to a decline in the quality of public services.